Assessing the effectiveness of learning management system implementation at a public university in Malawi - Mhango, Muyco (My University, 2025)
Many public and private universities across Malawi have deployed Learning Management Systems (LMSs) to respond to the Covid-19 pandemic. However, there is a paucity of studies that have been undertaken to understand the effectiveness of LMSs in Malawian universities. Therefore, the purpose of this study was to understand the effectiveness of Learning Management System implementation at a public university’s Open and Distance eLearning (ODeL) delivery mode. The study was guided by Information System Success Model (ISSM) and the three constructs of Technological Pedagogical Content Knowledge (TPACK) Framework as theoretical orientations. The study adopted pragmatism as a research philosophical underpinning, employing a cross-sectional survey design. First, data were gathered through the use of a survey questionnaire, distributed randomly to 151 students and 50 educators that had access to eLearning system. Second, interview schedule was conducted with sampled students, instructors, ICT technicians and centre managers of ODeL. Quantitative data collected were analysed descriptively using IBM SPSS, while qualitative data were manually analysed thematically based on the objectives of the study. The study found that the actual usage of eLearning system is limited. The study has also established that Moodle is meeting the standards of service quality, content quality and system quality. It was also revealed that while instructors possess fair technological competences, they have limited techno-content and techno-pedagogical skills which adversely affected their effective use of teaching via the Learning Management System. Despite the challenges observed, both instructors and students are moderately satisfied and have acknowledged various benefits accrued from utilization of the eLearning system. The findings contribute to theory and policy practice by informing online instructors, instructional designers, policymakers, and research practitioners on strategies for improving eLearning in expanding access to higher education in Malawi.
Keywords: Higher Education Institution; eLearning Platform; Adoption of Technology